Implementasi Dynamic Pricing dan Point System pada Aplikasi Pemesanan Air Minum Isi Ulang - Ragil Nur Rasyid; Yuli Asriningtias (STMIK Banjarbaru, 2025)
The increasing demand for refillable drinking water, driven by population growth and a practical lifestyle, creates the need for an efficient ordering system. On the other hand, the manual ordering process still faces constraints such as inefficient record-keeping, delivery delays, and a lack of incentives for loyal customers. This research focuses on developing a mobile-based water ordering application that integrates the concepts of dynamic pricing and a point system to improve operational efficiency and strengthen customer retention. The dynamic pricing model is implemented to adjust prices based on the time of ordering, while the point system is designed to encourage repeat transactions. The system was developed using Flutter for the user application and React with Firebase for the admin dashboard. System testing using the Black Box Testing method shows that the main system functionalities encompassing the ordering process, dynamic pricing calculation, and point system management have operated in accordance with the functional design.Keywords: Drinking water ordering; Dynamic pricing; point system; Mobile application; Flutter; Firebase AbstrakPermintaan air minum isi ulang yang meningkat akibat pertumbuhan populasi dan gaya hidup praktis menimbulkan kebutuhan akan sistem pemesanan yang efisien. Di sisi lain, proses pemesanan manual masih menghadapi kendala seperti ketidakefisienan pencatatan, keterlambatan pengiriman, dan kurangnya insentif bagi pelanggan setia. Penelitian ini berfokus pada pengembangan aplikasi pemesanan air minum berbasis mobile yang mengintegrasikan konsep dynamic pricing dan point system guna meningkatkan efisiensi operasional serta memperkuat retensi pelanggan. Model dynamic pricing diterapkan guna menyesuaikan harga berdasarkan waktu pemesanan, sedangkan point system dirancang untuk mendorong transaksi berulang. Sistem dikembangkan menggunakan Flutter sebagai aplikasi pengguna dan React dengan Firebase untuk dashboard admin. Pengujian sistem menggunakan metode Black Box Testing menunjukkan bahwa fungsionalitas utama sistem mencakup proses pemesanan, kalkulasi dynamic pricing, dan pengelolaan point system telah berjalan sesuai dengan rancangan fungsional.